Internalisasi Nilai-Nilai Adab dalam Pembelajaran Pendidikan Agama Islam dan Implikasinya terhadap Prestasi Belajar Siswa di SMPIT Ar-Risalah Surakarta: Sebuah Telaah Kajian Pustaka - Jumingan Jumingan; Joko Subando (TSAQOFAH, 2026)
The internalization of adab values in Islamic Religious Education (PAI) learning plays an important role in shaping students’ character, discipline, and quality of learning, particularly in the context of integrated Islamic schools. This study aims to analyze the process of internalizing adab values in PAI learning and its implications for students’ learning achievement at SMPIT Ar-Risalah Surakarta. This study used a qualitative approach through library research by examining various scientific literature, books, journal articles, and previous research findings relevant to adab education, Islamic character education, and learning achievement. The results of the review showed that the internalization of adab values in PAI learning can be carried out through habituation, role modeling, value integration in the learning process, and the strengthening of school culture. The implementation of adab education contributes positively to students’ cognitive, affective, and psychomotor development. In addition, the internalization of adab values is able to improve students’ learning discipline, learning motivation, responsibility, and academic achievement. These findings contribute to strengthening the theoretical foundation regarding the relationship between adab education and students’ learning achievement in the context of integrated Islamic schools. The conclusion of this study affirms that the internalization of adab values in PAI learning functions not only as a reinforcement of Islamic character but also as a pedagogical strategy to support the improvement of students’ learning quality.